When Intimate Partner Violence Meets Same Sex Couples: A Review of Same Sex Intimate Partner Violence - Rollè, Luca; Giardina, Giulia; Caldarera, Angela M.; Gerino, Eva; Brustia, Piera (Frontiers in Psychology, 2018)
Over the past few decades, the causes of and intervention for Intimate Partner Violence (IPV) have been approached and studied. This paper presents a narrative review on IPV occurring in same sex couples, that is, same sex IPV (SSIPV). Despite the myth that IPV is exclusively an issue in heterosexual relationships, many studies have revealed the existence of IPV among lesbian and gay couples, and its incidence is comparable to (Turell, 2000) or higher than that among heterosexual couples (Kelley et al., 2012; Messinger, 2011). While similarities between heterosexual and lesbian, gay, and bisexual (LGB) IPV were found, unique features and dynamics were present in LGB IPV. Such features are mainly related to identification and treatment of SSIPV in the community and to the need of taking into consideration the role of sexual minority stressors. Our findings show there is a lack of studies that address LGB individuals involved in IPV; this is mostly due to the silence that has historically existed around violence in the LGB community, a silence built on fears and myths that have obstructed a public discussion on the phenomenon. We identified the main themes discussed in the published studies that we have reviewed here. The reviews lead us to the conclusion that it is essential to create a place where this subject can be freely discussed and approached, both by LGB and heterosexual people.